Expanded Regulatory T Cells Induce Alternatively Activated Monocytes With a Reduced Capacity to Expand T Helper-17 Cells - Romano, Marco; Fanelli, Giorgia; Tan, Nicole; Nova-Lamperti, Estefania; McGregor, Reuben; Lechler, Robert I.; Lombardi, Giovanna; Scottà, Cristiano (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are essential in maintaining peripheral immunological tolerance by modulating several subsets of the immune system including monocytes. Under inflammatory conditions, monocytes migrate into the tissues, where they differentiate into dendritic cells or tissue-resident macrophages. As a result of their context-dependent plasticity, monocytes have been implicated in the development/progression of graft-vs-host disease (GvHD), autoimmune diseases and allograft rejection. In the last decade, Tregs have been exploited for their use in cell therapy with the aim to induce tolerance after solid organ transplantation and for the treatment of autoimmune diseases and GvHD. To date, safety and feasibility of Treg infusion has been demonstrated; however, many questions of how these cells induce tolerance have been raised and need to be answered. As monocytes constitute the major cellular component in inflamed tissues, we have developed an in vitro model to test how Tregs modulate their phenotype and function. We demonstrated that expanded Tregs can drive monocytes toward an alternatively activated state more efficiently than freshly isolated Tregs. The effect of expanded Tregs on monocytes led to a reduced production of pro-inflammatory cytokines (IL-6 and tumor necrosis factor-α) and NF-κB activation. Furthermore, monocytes co-cultured with expanded Tregs downregulated the expression of co-stimulatory and MHC-class II molecules with a concomitant upregulation of M2 macrophage specific markers, CD206, heme oxygenase-1, and increased interleukin-10 production. Importantly, monocytes co-cultured with expanded Tregs showed a reduced capacity to expand IL-17-producing T cells compared with monocyte cultured with freshly isolated Tregs and conventional T cells. The capacity to decrease the expansion of pro-inflammatory Th-17 was not cytokine mediated but the consequence of their lower expression of the co-stimulatory molecule CD86. Our data suggest that expanded Tregs have the capacity to induce phenotypical and functional changes in monocytes that might be crucial for tolerance induction in transplantation and the prevention/treatment of GvHD and autoimmune diseases.